2010
DOI: 10.1242/jeb.037689
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced hypoglycaemia is co-ordinately regulated by liver and muscle during acute and chronic insulin stimulation in rainbow trout (Oncorhynchus mykiss)

Abstract: SUMMARYThe relative glucose intolerance of carnivorous fish species is often proposed to be a result of poor peripheral insulin action or possibly insulin resistance. In the present study, data from aortic cannulated rainbow trout receiving bovine insulin (75 mIU kg -1 ) injections show for the first time their ability to clear glucose in a very efficient manner. In another set of experiments, mRNA transcripts and protein phosphorylation status of proteins controlling glycaemia and glucose-related metabolism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
65
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 53 publications
13
65
3
Order By: Relevance
“…Despite this reduced activity of glucose phosphorylating enzymes in the liver of trout fed the HFD, hepatic glycogen levels increased, favouring the idea that the storage of excess glucose as hepatic glycogen does not actually contribute to the control of glycaemia but simply reflects the glycaemic profile. This concept is not new in trout and has been observed recently in insulin-induced hypoglycaemic fish (Polakof et al, 2010). In both muscle and WAT, where gluconeogenesis plays a minor role, the inhibition of HK by the HFD was accompanied by depleted glycogen levels.…”
Section: Metabolic Events Linked To the Hfd-induced Hyperglycaemiamentioning
confidence: 89%
See 3 more Smart Citations
“…Despite this reduced activity of glucose phosphorylating enzymes in the liver of trout fed the HFD, hepatic glycogen levels increased, favouring the idea that the storage of excess glucose as hepatic glycogen does not actually contribute to the control of glycaemia but simply reflects the glycaemic profile. This concept is not new in trout and has been observed recently in insulin-induced hypoglycaemic fish (Polakof et al, 2010). In both muscle and WAT, where gluconeogenesis plays a minor role, the inhibition of HK by the HFD was accompanied by depleted glycogen levels.…”
Section: Metabolic Events Linked To the Hfd-induced Hyperglycaemiamentioning
confidence: 89%
“…Insulin receptor substrate 1 (IRS1) and Akt protein level was assessed in the skeletal muscle, the main insulin-sensitive tissue. Anti-phosphoAkt Ser473 (Polakof et al, 2010), anti--tubulin (Polakof et al, 2010) and anti-IRS1 (Seiliez et al, 2011) have been shown to successfully cross-react with rainbow trout Akt, -tubulin and IRS1 protein, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, injection of insulin in rainbow trout surprisingly reduced the level of GK gene expression in contrast to mammals and birds, even though insulin has a clear hypoglycaemic mammalian-type effect (217,237,238) . These data were confirmed using micro-osmotic pumps with insulin; the chronic infusion of insulin reduced also the level of GK mRNA (237) . Using rainbow trout hepatocytes, the same antagonist results of glucose and insulin on GK gene expression have been also shown.…”
Section: Glucokinase In Different Speciesmentioning
confidence: 94%